Pengaruh Profesionalitas Kerja dan Komitmen Organisasi Terhadap Kinerja Pegawai Dinas Komunikasi, Informatika, Statistik dan Persandian Kota Bekasi Tahun 2022 - Parjaya Parjaya; Wahidin Septa Zahran (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of this study is to determine the how much influence of work professionality and organizational commitment on employee performance in Department of Communication, Information, Statistics and Code of Bekasi City. The research method used is quantitative research in the form of survey. Samples this research are 97 employee. Methods of data collection using questionnaires with likert scale. Conclusion this study : (1) influence of work professionality on employee performance, regression line ????̂ = -0,661 + 0,804X1. Hypothesis test with t-test result obtained by Sig. = 0,000 and tcount = 37,564 > ttable = 1,661, H0 reject; (2) influence of organizational commitment on employee performance, regression line ????̂ = 1,864 + 0,840X2. Hypothesis test with t-test result obtained by Sig. = 0,000 and tcount = 31,403 > ttable = 1,661, H0 reject; (3) influence of work professionality and organizational commitment on employee performance, regression line ????̂ = - 0,734 + 0,495X1 + 0,350X2. Hypothesis test with F-test result obtained by Sig. = 0,000 and Fcount = 1045,360 > Ftable = 3,093, H0 reject. Conclusion of this research : (1) work professionality strong positive influence and significant on employee performance; (2) organizational commitment strong positive influence and significant on employee performance; (3) work professionality and organizational commitment together strong positive influence and significant on employee performance.